Targeting of Immune Cells by Dual TLR2/7 Ligands Suppresses Features of Allergic Th2 Immune Responses in Mice. (24th October 2017) - Laiño, Jonathan; Wangorsch, Andrea; Blanco, Frank; Wolfheimer, Sonja; Krause, Maren; Flaczyk, Adam; Möller, Tobias-Maximilian; Tsai, Mindy; Galli, Stephen; Vieths, Stefan; Toda, Masako; Scheurer, Stephan; et al.
Abstract : Background . TLR ligands can promote Th1-biased immune responses, mimicking potent stimuli of viruses and bacteria. Aim . To investigate the adjuvant properties of dual TLR2/7 ligands compared to those of the mixture of both single ligands. Methods . Dual TLR2/7 ligands: CL401, CL413, and CL531, including CL264 (TLR7-ligand) and Pam2 CysK4 (TLR2-ligand), were used. Immune-modulatory capacity of the dual ligands with the individual ligands alone or as a mixture in mouse BMmDCs, BMmDC:TC cocultures, or BMCMCs was compared and assessed in naïve mice and in a mouse model of OVA-induced intestinal allergy. Results . CL413 and CL531 induced BMmDC-derived IL-10 secretion, suppressed rOVA-induced IL-5 secretion from OVA-specific DO11.10 CD4 + TCs, and induced proinflammatory cytokine secretion in vivo . In contrast, CL401 induced considerably less IL-10 secretion and led to IL-17A production in BMmDC:TC cocultures, but not BMCMC IL-6 secretion, or IL-6 or TNF- α production in vivo . No immune-modulating effects were observed with single ligands. All dual TLR2/7 ligands suppressed DNP-induced IgE-and-Ag-specific mast cell degranulation. Compared to vaccination with OVA, vaccination with the mixture CL531 and OVA, significantly suppressed OVA-specific IgE production in the intestinal allergy model. Conclusions . Based on beneficial immune-modulating properties, CL413 and CL531 may have utility as potential adjuvants for allergy treatment.